Fostering students’ peer relationships through the classroom-based intervention FRIEND-SHIP. Education 3-13 - Hassani, S.; Jakob, K.; Schwab, S.; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze (International Journal of Primary, Elementary and Early Years Education.)
Keywords: Life-span and Life-course Studies; Education

Characterizing external visualization in mathematics education research: a scoping review - Schoenherr, Johanna; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract External visualization (i.e., physically embodied visualization) is central to the teaching and learning of mathematics. As external visualization is an important part of mathematics at all levels of education, it is diverse, and research on external visualization has become a wide and complex field. The aim of this scoping review is to characterize external visualizations in recent mathematics education research in order to develop a common ground and guide future research. A qualitative content analysis of the full texts of 130 studies published between 2018 and 2022 applied a deductive-inductive coding procedure to assess four dimensions: visualization product or process, type of visualization, media, and purpose. The analysis revealed different types of external visualizations including visualizations with physical resemblance ranging from pictorial to abstract visualizations as well as three types of visualizations with structural resemblance: length, area, and relational visualizations. Future research should include measures of visualization products or processes to help explain the demands and affordances that different types of visualizations present to learners and teachers.
Keywords: General Mathematics; Education

Research Approaches on Workplace Learning
The volume comprises a variety of research approaches that seek to explore and understand employees’ learning and development through and for work. Working life reveals challenges through technological, economic and societal development that can only rudimentarily be addressed by formal education and training. Workplace learning becomes more and more important for employees and enterprises to successfully cope with these challenges. Workplace learning is a steadily growing field of educational research but it lacks so far a scholastic canon – there is rather a diversity of research approaches. This volume reflects this diversity by bringing together researchers from different countries and different theoretical backgrounds, presenting their current research on topics that all are relevant for understanding presages, processes and outcomes of workplace learning. Hence, this volume is of relevance for researchers as well as practitioners in the field and policy makers.
Keywords: tivesTeam learningTeam climateSocial influences on team learningKnowledge construction in teamsLearning cultureAcknowledgement of competencesTechnology and professional learningCreation of a learning eco-systemDiversity as a challenge for organisationsHigher education as preparation for WPLSocial support in networks and professional learningvocational and professional education

Supporting Young Immigrants in Their Transition From School to Work? A Staff Perspective on Challenges of Vocational Integration Classes - Goller, Michael (International Journal for Research in Vocational Education and Training)
Context: The implementation of successful measures to support immigrants' integration in cultural, social, and economic life can be considered as one of today's greatest challenges for many societies. This is especially true for adolescent immigrants who have not yet been able to finish education or gain qualifications relevant to joining the labour market. That is why many receiving countries have developed and implemented special programmes that aim at supporting immigrants' integration by facilitating their employability. Unfortunately, not much is known about the process of implementing these programmes or about how education systems, schools, and teachers are dealing with the new situation and target group. In this contribution, the implementation, development, and challenges of German Vocational Integration Classes (VIC), as an example of comparable programmes in the EU, are investigated to address this research gap. The paper considers the following exploratory research questions: (a) What challenges have been experienced by teachers and social workers in the implementation of VIC as well as in the integration of immigrants into the labour market in recent years? (b) How can these challenges be met in the long run and how should VIC be developed to better achieve its aims? Methods: To answer these questions, a sequential qualitative study containing questionnaire and interview elements was conducted. First, teachers and social workers involved in VIC filled in a questionnaire about their experiences and experienced challenges in implementing VIC (N = 46). Then, supplementing interviews were conducted with participants from the first sample in order to generate further insights and to contextualise the findings from the first study part (N = 14). Findings: From the respondents' answers, it appears that the VIC programme is well implemented. The results show, however, that central challenges continue to exist. This concerns, for example, legal regulations or the development of adequate curricula, but also the scope and quality of language education. In addition, problems have also been identified with regard to students' culture-specific education and their individual attitudes. These prevailing problems seem to affect schooling and educational processes. In addition, respondents report feeling left alone to deal with problems and that their experiences from their daily work in VIC and with immigrants are not sufficiently taken into account in policy and school-related decisions. Conclusions: Although VIC seems well implemented, key challenges remain in the view of the participants. It was found that teachers cannot solve many of the identified problems themselves, as they require action at the level of policy or school organisation. For staff, this can be accompanied by increased stress and demotivation. For the young immigrants, the existing challenges can have a long-term impact on school success and transition to vocational education and training. The study thus highlights the importance of targeted and holistic strategies to support immigrant integration through education.
Keywords: Immigration; Educational Policy; Employability; Mixed Methods; VET; Vocational Education and Training; Transitions From Education and Training to Employment

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; Hüsing, Sven; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

Die professionelle pädagogische Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften: Belastungsfaktor oder Ressource? - Kärner, Tobias; Goller, Michael; Bonnes, Caroline; Maué, Elisabeth (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung: Der Beitrag befasst sich mit der professionellen pädagogischen Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften, deren Beitrag für die Beanspruchung der Referendar*innen bisher noch nicht eingängig untersucht wurde. Das Ziel der Studie ist es, anhand einer Querschnittserhebung von 2583 Referendar*innen und ausgebildeten Lehrkräften, kompensatorische sowie verstärkende Effekte der Beziehungsdimensionen Transparenz, Fairness, Vertrauen und Ambivalenz auf die wahrgenommene Beanspruchung im Referendariat zu untersuchen. Die Analyse erfolgt mittels eines latent moderierten Strukturgleichungsansatzes. Die Ergebnisse zeigen, dass Belastungen durch die Kerntätigkeiten im Referendariat sowie Belastungen durch den Umgang mit Kolleg*innen im Lehrer*innenkollegium in signifikant positivem Zusammenhang mit resultierenden Beanspruchungsreaktionen stehen. Je transparenter, fairer und vertrauensvoller und je weniger ambivalent die Beziehung zur Seminarlehrkraft erlebt wird, desto geringer fallen die Beanspruchungsreaktionen aus. Die Ergebnisse werden hinsichtlich ihrer Relevanz für die Beziehungsarbeit im Referendariat als zentralem Ausbildungsbestandteil der zweiten Phase der Lehrer*innenausbildung diskutiert.
Keywords: Education

Rekonstruktive Evaluationsforschung im Kontext praxeologischer Kompetenzdiskurse. Kritische Reflexionen und konzeptionelle Überlegungen zur Dokumentarischen Evaluationsforschung - Bloh, Thiemo (Zeitschrift für Evaluation)
Praxeologische Kompetenzansätze verstehen Kompetenz als sozial erlernt und folglich als relativ zum sozialen Kontext. Damit einher geht die Frage, wie solche praxeologisch gerahmten Kompetenzen eigentlich unabhängig von der sie hervorbringenden Praxis evaluiert werden können – und eben dadurch erst für einen breiteren Kompetenzdiskurs fruchtbar sind. Die Dokumentarische Evaluationsforschung bietet hierzu erste Anhaltspunkte, offenbart aber auch Grenzen, die mit dem Evaluationsverständnis zusammenhängen, sich jedoch in der Forschungspraxis so nicht finden lassen. Aus der Differenz zwischen Methode und Praxis dokumentarischer Evaluation lässt sich formulieren, wie eine praxeologische Evaluation gestaltet werden könnte. Dabei spielt die Formulierung von Referenzrahmen eine zentrale Rolle, welche einerseits der zu evaluierenden Praktik external sein, andererseits praktisch formuliert werden müssen, damit sie soziale Praktiken jenseits ihrer eigenen Sinnhaftigkeit evaluativ (er-)fassen können.
Keywords: Strategy and Management; Applied Psychology; Social Sciences (miscellaneous); Education; Communication; Statistics and Probability

Von der Not zur Tugend!? - Caruso, Carina; Bruns, Marike; Harteis, Christian (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s) Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Der Begriff der „Zwangsdigitalisierung“ beschreibt, dass als eine Folge der Corona-Pandemie Präsenzformate durch digital gestützte Settings ersetzt werden sowie Alter- nativen zur Kommunikation und für das gemeinsame Arbeiten und Lernen in Präsenz gefunden werden mussten. Digital gestützte Lehr-Lernsettings scheinen seit dem ersten Lockdown sowohl an Schulen als auch an Hochschulen eine Möglichkeit dafür darzustellen, die Lern- und Entwicklungsprozesse (z. B. von Schülerinnen und Schülern, angehenden Lehrkräften) trotz physischer Distanz weiterzuführen. In diesem Beitrag werden die mit der Zwangsdigitalisierung an den Hochschulen verbundenen Chancen und Grenzen für die Entwicklung digitalisierungsbezogener Kompetenzen angehender Lehrkräfte herausgearbeitet. Dabei richtet sich der Blick auf den Wert von Erfahrungen für Lernen und Entwicklung. Zudem wird, gemäß der den Angebots-Nutzungs-Modellen inhärenten Logik einer „Wirkkette“, Bezug genommen auf Perspektiven von Studierenden, deren prospektiven Schülerinnen und Schülern sowie von Dozierenden.
Keywords: Hochschullehre; Lehrer:innenausbildung; Medienkompetenz / teacher education; teaching at university; media literacy

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for researching professional learning and development: Challenges, applications and empirical illustrations)
Q is an exploratory method used to elicit discrete patterns of subjectivity (e.g., subjective theories, beliefs). To be more concrete, Q method aims to identify homogeneous latent clusters of viewpoints towards a certain topic from a larger more heterogeneous set of (a priori unknown) different viewpoints held by respondents in the population. For this purpose, study participants are asked to sort qualitative statements concerning a certain topic (e.g., their beliefs toward something) into a grid roughly following a normal distribution indicating whether they agree or disagree with the given propositions. This results in a so-called Q-sort for each participant that then can be fed into a factor analysis that compares the different Q-sorts and groups them by similarity. In the first part of the chapter, Q method is introduced. The second part of the chapter describes a small study focusing on student teachers and their perspectives concerning upcoming long-term school internships.
Keywords: Q method; Subjectivity; Internships; Teacher education; Q sort

Effects of school closures during the COVID-19 pandemic in early 2020 on prospective teachers in a one-semester school internship - Vogelsang, Christoph; Wiethoff, Christoph (European Journal of Teacher Education)
Keywords: Education

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Learning to Plan by Learning to Reflect?—Exploring Relations between Professional Knowledge, Reflection Skills, and Planning Skills of Preservice Physics Teachers in a One-Semester Field Experience - Vogelsang, Christoph; Kulgemeyer, Christoph; Riese, Josef (Education Sciences)
Following concepts describing lesson planning as a form of anticipatory reflection, preservice physics teachers’ reflection skills are assumed to be positively connected with their planning skills. However, empirical evidence on this is scarce. To explore how relations between these specific skills change over the course of a field experience controlling for influences of professional knowledge, we conduct a pre-post field study with N = 95 preservice physics teachers in a one-semester field experience. Content knowledge (CK) and pedagogical content knowledge (PCK) (paper-and-pencil tests), and reflection and planning skills (standardized performance assessments) were assessed before and after the field experience. Path analyses revealed almost no influence of reflection skills on planning skills. Reflections skills did not contribute to preservice teachers planning skills beyond knowledge, indicating both constructs might represent rather independent abilities. The results show the need for further development of models describing the development of teachers’ professional knowledge and skills in academic teacher education and for the development of concepts for a better integration of reflection and lesson planning in field experiences.
Keywords: Public Administration; Developmental and Educational Psychology; Education; Computer Science Applications; Computer Science (miscellaneous); Physical Therapy; Sports Therapy and Rehabilitation

Exploring the effects of physics explainer videos and written explanations on declarative knowledge and the illusion of understanding - Kulgemeyer, Christoph; Hörnlein, Madeleine; Sterzing, Fabian (International Journal of Science Education)
Keywords: Education

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Comparing tablet and print mode of a german reading comprehension test in grade 3: Influence of test order, gender and language - Seifert, Susanne; Paleczek, Lisa (International Journal of Educational Research)
Keywords: Education

Bending and Bowing: How Teachers Adapt a Vocabulary-Based Reading Program to Their Students Needs - Kulmhofer-Bommer, Andrea; Seifert, Susanne; Paleczek, Lisa; Gasteiger-Klicpera, Barbara (Journal of Education)
This paper investigates the implementation of a reading program designed for third grade elementary school classrooms in Austria. Using a mixed-methods approach, lesson types were identified, respective class compositions analyzed, and the effects on students’ reading gains examined. The results show that the lesson types seem to reflect learner group needs as students in the different lesson types profited similarly from the reading program. This supports the hypothesis that reading is a highly individualized process and leads to the conclusion that the instructional approach of the reading program investigated supports teachers in conducting reading lessons tailored to their students’ needs.
Keywords: Education

A feasibility study of digital content use in inclusive, Austrian primary school practice - Paleczek, Lisa; Ender, Daniela; Berger, Jessica; Prinz, Katharina; Seifert, Susanne (International Journal of Educational Research)
Keywords: Education

First-year university students' self-regulated learning during the COVID-19 pandemic: a qualitative longitudinal study - Liebendörfer, Michael; Kempen, Leander; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract When the COVID-19 pandemic began, many universities switched to fully online teaching. This unexpected switching to online teaching was challenging for both teachers and students, and restrictions that were put in place because of pandemic made this challenge even greater. However, new ways of teaching might also open new opportunities for students’ learning. The research question driving our study was as follows: how do students regulate their learning and specifically their choice of resources and peer learning in university mathematics classes that are fully taught online as offered during the COVID-19 pandemic? We report on a longitudinal, qualitative study in which students recorded a brief audio diary twice a week over one whole semester (14 weeks). We focused on three students who completed 70 interviews in total and finished the semester with varying degrees of success. The results show how the students structured their studying (e.g., the roles that deadlines or synchronous teaching events played). They illustrate the strengths and limitations of digital materials provided by the lecturer and the use of complementary media. Further, the pandemic uncovered the double-edged role of simple, often anonymous exchanges (e.g., via Discord servers), with few binding forces for either side, and the significance of stable learning partnerships for students’ success. Our research highlights aspects that should be focal points when comparing traditional instruction and online instruction during the pandemic from a self-regulatory perspective. Practical implications refer to how these aspects can be combined sensibly in fully online courses, but also in blended learning contexts.
Keywords: General Mathematics; Education

Exploring the Perceived Relevance of University Mathematics Studies by First-Semester Teaching Students - Büdenbender-Kuklinski, Christiane; Hochmuth, Reinhard; Liebendörfer, Michael (International Journal of Research in Undergraduate Mathematics Education)
Abstract As earlier research results suggest that many mathematics teaching students criticize a missing relevance in their studies, we explore explanations and interrelationships of their relevance assessments. We aim at finding out how one could support the students in attributing relevance to their study programs. A two-fold model for relevance assessments in mathematics teacher education is proposed, consisting of relevance content and relevance reasons. We investigate students' relevance perceptions of mathematical topics and of topics’ complexities, as well as their rating of individual and societal/ vocational relevance reasons, all in relation to their perception of the relevance of their overall program of study. Contrary to earlier research findings, our results suggest that mathematics teaching students already do attribute relevance to many content areas and that a preparation for the teaching profession is not the only reason for them to assign relevance. There also seem to be many students who would attribute relevance if they could develop as individuals and pursue their interests. We suggest that giving students opportunities to set individual priorities in their studies could hence support their relevance assessments. As low relevance assessments seem to be connected to students’ motivational problems, students might profit from motivational support, as well.
Keywords: Education; Mathematics (miscellaneous)

Messung von Unterrichtsplanungskompetenz im Fach Sachunterricht: Empirische Befunde zur Kompetenzentwicklung angehender Grundschullehrkräfte auf Grundlage einer mehrdimensionalen Kompetenzstruktur - Kirsch, Alexander (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im vorliegenden Beitrag werden nach ausführlicher theoretischer Diskussion des Kompetenzbegriffs und der Definition von Kompetenz als Können ein Modell sachunterrichtlicher Planungskompetenz sowie ein daran anschließendes Messinstrument vorgestellt. Im Hinblick auf den Einsatz dieses Instrumentes im Rahmen einer Evaluation des nordrhein-westfälischen Praxissemesters stellen sich Fragen nach der psychometrischen Struktur der Testauswertung. Da das Instrument sowohl zur Testung von Sachunterrichtsstudierenden mit dem Lehramtsprofil ‚Grundschule‘ als auch von Sachunterrichtsstudierenden mit sonderpädagogischem Schwerpunkt eingesetzt werden soll, ist zu zeigen, dass die Testergebnisse nicht durch den gewählten Studiengang beeinflusst werden. Im Beitrag werden Rohdaten aus einer Studie an der Universität Paderborn ( n = 121) genutzt, um eine fünfdimensionale Modellstruktur gegen eine eindimensionale zu testen und empirisch gestützte Argumente für eine mehrdimensionale Skalierung zu generieren. Durch Differential-Item-Functioning-Analysen wird geprüft, ob die Itemschwierigkeiten mit dem Merkmal ‚Studiengang‘ interagieren, sodass sie sich trotz gleicher Kompetenzausprägung für Untersuchungsteilnehmende beider Studierendengruppen signifikant unterscheiden und zu einer diagnostischen Verzerrung führen würden. Abschließend wird der beispielhafte Einsatz des Instrumentes im Rahmen einer Wirksamkeitsanalyse in Bezug die Effektivität des nordrhein-westfälischen Praxissemesters an der Universität Paderborn ( n = 26) dargelegt. Aus den differenzierten Ergebnissen werden unter anderem erste Hinweise auf Defizite in der Lehrerinnen- und Lehrerausbildung abgeleitet.
Keywords: Education

Entwicklung und Evaluation eines Fortbildungskonzepts im Kontext der technischen Bildung an Grundschulen am Beispiel von Lernrobotern - Janicki, Nicole (Technik: Verstehen wir, was wir nutzen!? - Tagungsband zur 23. Jahrestagung der Deutschen Gesellschaft für Technische Bildung in Mannheim vom 24.-25. September 2021.)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

The role of ICT for school leadership and management activities: an international comparison - Tulowitzki, Pierre; Gerick, Julia; Eickelmann, Birgit (International Journal of Educational Management)
Purpose Information and communication technologies (ICT) has an increasing impact on schools. School leaders play a key role in this context as drivers of innovation including those related to ICT. Against this background, the study presented in this article focuses on school leadership and management activities with ICT and related challenges. It sought to analyze how frequently German school principals use ICT compared to principals in other countries, what distinct clusters of German principals could be identified in terms of ICT usage and how principals viewed ICT in schools and related challenges. Design/methodology/approach A mixed-methods approach was chosen, using quantitative data from both the international comparative large-scale assessment study ICILS 2018 and the explorative qualitative data from Germany. For the international comparison, the school principal data sets of the 12 international participants of the International Computer and Information Literacy Study (ICILS) 2018 were taken into account: Chile, Denmark, Finland, France, Germany, Italy, Kazakhstan, Republic of Korea, Luxembourg, Portugal, Uruguay and the United States. To look beyond averaged frequencies, a latent class analysis (LCA) was conducted to identify possible clusters of school leaders with distinct usage patterns of ICT for leadership and management activities. Findings The results indicate that, in general, German principals use ICT for leadership and management activities on a similar level as their international colleagues. However, they seem to communicate with education authorities significantly more often than their international colleagues, whereas representative activities (presentations, home page) are rather infrequent. The qualitative data point to significant barriers to fully harnessing the potential of using ICT for leadership, management and school improvement such as lack of competencies and lack of adequate support. Originality/value To the best of the authors’ knowledge, this is the first study that focuses on school leadership and management activities using ICT with such a data set. The results provide insights into how German principals use ICT to lead and manage their schools compared to their international counterparts. The qualitative data offers additional insights into possible reasons hindering a more effective use of ICT.
Keywords: Organizational Behavior and Human Resource Management; Education; Organizational Behavior and Human Resource Management; Education

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Development and validation of a video-based test instrument to measure noticing with regard to processes ofrecognition in inclusive physical education - Langer, Wiebke; Bruns, Julia; Erhorn, Jan (German Journal of Exercise and Sport Research)
The construct of noticing is considered to be of crucial importance for professional action of (prospective) physical education (PE) teachers in the context of (inclusive) PE. In order to implement the demands of inclusive PE teaching, noticingwith regard to processes of recognition proves to be particularly significant. Due to the relevance of physicality, the design of recognition relationships that encourage pupils' development results in specific requirements for the selective attention and the theory-based interpretation of processes of recognition and disregard in complex teaching situations. This facet of competence has hardly been studied so far, partly due to the lack of instruments for standardised assessment of this construct. In the context of this paper, the development and validation of a standardised, video vignette-based test instrument for the measurement of noticingwith regard to processes of recognition of prospective PE teachers is presented. The validation focuses on the content of the test and the internal structure of the instrument as well as on correlations with related constructs in terms of content. The results from three consecutive validation studies provide indications of the reliability and validity of the test score interpretation of the instrument ViProQiS_A. The findings so far indicate that the standardised measurement of noticingwith regard to processes of recognitionin inclusive PE could be realized on the basis of the test instrument developed here.
Keywords: Physical education teacher education; Competence modelling and; measurement; Inclusive physical education; Video-based items; Noticing

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Labor market spillover effects of a compulsory schooling reform in Germany - Schiele, Valentin
Compulsory schooling reforms are often used to estimate monetary returns to education. Such reforms are unrelated to individual characteristics and preferences and thus arguably able to eliminate selection bias. However, as these reforms affect a large number of individuals in the relevant age groups, they might have spillover effects on individuals not directly affected by the reform. Such spillover effects constitute a problem for identification and estimation of returns to schooling. As they are difficult to address, they are mostly ignored in the empirical literature. I show that the introduction of the compulsory ninth grade in Germany led to a labor supply shock that might have increased wages and employment of individuals who were not directly subject to the reform and were assumed not to be affected in previous research. To investigate in this kinds of spillover effects, I exploit the staggered introduction of the compulsory ninth grade across German federal states in a difference-in-differences approach. Based on large scale register and survey data, I find no evidence for persistent spillover effects for men. For women, however, my results suggest that the labor supply shock resulting from the reform may have led to a persistent increase in employment and wages.
Keywords: Compulsory schooling; Education; Spillover effects; Cohort size; Wages; Employment

Group work and student procrastination - Koppenborg, Markus; Klingsieck, Katrin B. (Learning and Individual Differences)
Keywords: Developmental and Educational Psychology; Education; Social Psychology

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; HÜSING, SVEN; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Prospective Teachers’ Diagnostic Thinking on Students’ Understanding of Multi-Digit Multiplication: A Content-Related Analysis on Unpacking of Knowledge Elements - Dröse, Jennifer; Prediger, Susanne (Journal für Mathematik-Didaktik)
Abstract Teachers’ in-depth diagnostic thinking has been shown to be crucial for student-centered teaching as they need to perceive and interpret students’ understanding for well-informed decision-making on adaptive teaching practices. The paper presents a content-related approach to analyzing diagnostic thinking processes with respect to the mathematical knowledge elements that prospective teachers identify as students’ resources and obstacles. Prospective teachers’ challenge is that some relevant knowledge elements first have to be unpacked, because compact concepts (such as the place value concept) or procedures (such as for multi-digit multiplication) comprise several smaller knowledge elements (such as the positional property) that have to be made explicit for students to foster their learning processes adequately. Our study examines what knowledge elements prospective teachers perceive and interpret in a transcript vignettes on multi-digit multiplication (of decimal and natural numbers) and its underlying basic arithmetic concepts (place value understanding and meaning of multiplication) in written diagnostic judgments on students’ resources and obstacles ( N = 196). A comparative design within the vignette is used to investigate how far the process of perceiving can be supported by thematic cues. The analysis reveals that those knowledge elements cued in the vignette by being already unpacked and explicitly addressed are perceived and interpreted more often (but with lower correctness) than those that are uncued and therefore have to be unpacked by the prospective teachers themselves. This confirms the need to prepare prospective teachers for unpacking mathematical concepts themselves.
Keywords: Education; General Mathematics

Organisation der dualen Berufsausbildung zum/zur Verkäufer:in und Kaufmann:frau im Einzelhandel im Zeichen der COVID-19-Pandemie. - Sommer, Christian; Szczesny, Daniela (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern.)
One of the most powerful events in the still young 21st century is certainly the outbreak of the coronavirus and the following COVID-19 pandemic. Massive economic as well as social distress caused worldwide devastation. In Germany, not only stores, factories, cultural facilities were closed, but also – for the first time in history – schools were closed nationwide. Closed working sites and vocational schools, as well as working sites, which remained open due to their systemic relevance, led to so far unknown challenges in Germany’s vocational education system. A very good example are the dual apprenticeships, such as trained retail salesman, which were only partially affected by closures. The main goal of education policy was to compensate personal communication and interaction via digital media. This article’s main aim is to reveal the strategies vocational schools have developed to overcome the challenges they had to face because of the pandemic.
Keywords: COVID-19; Digitalization; Vocational education and training; Retail

Ein kritisch-multiperspektivischer Blick auf Forschendes Lernen in der Lehrkräftebildung - Bloh, Thiemo; Caruso, Carina (die hochschullehre)
Forschendes Lernen in der Lehrer:innenbildung ist seit der Ausweitung schulpraktischer Anteile bzw. der Einführung des sogenannten Praxissemesters eng verwoben mit der Lehrer:innenausbildung. Gleichzeitig wird bisher weitestgehend different beantwortet, was Forschendes Lernen ist und sein kann sowie warum es wie hochschuldidaktisch gerahmt wird und werden sollte. Der Beitrag widmet sich dieser Frage. Dabei zeigt sich einerseits, dass hochschuldidaktische Zugänge zur Realisierung Forschenden Lernens in der Lehrer:innenbildung erst vor dem Hintergrund theoretischer Annahmen zur Entwicklung von Lehrpersonen und deren Professionalität sowie zur Gestalt - gemeint ist hier der Beitrag zu dieser Entwicklung sowie der Anteil an Professionalität - Forschenden Lernens entwickelt werden können, eine solche Fundierung aber oftmals ausbleibt. Andererseits wird herausgearbeitet, inwiefern eine Differenz zwischen wissenschaftlicher Forschung und Forschung im Forschenden Lernen besteht. Daran anschließend wird eine habitustheoretische Fundierung Forschenden Lernens vorgestellt und es werden exemplarisch deren Implikationen für die Gestaltung Forschenden Lernens benannt. Abschließend wird anhand empirischer Rekonstruktionen beispielhaft eine praktische Umsetzung diskutiert.
Keywords: Forschendes Lernen; Lehrer:innenausbildung; Praxissemester; Professionalisierung / Research-based learning; teacher education; internships; professionalization

Scaffolding Close Reading of Mathematical Text in Pre-service Primary Teacher Education at the Tertiary Level: Design and Evaluation - Rezat, Sebastian; Malik, Sara Naseem; Leifeld, Markus (International Journal of Science and Mathematics Education)
Abstract Even in the digital age, learning mathematics at an academic level still requires much reading of mathematical text. Research has shown that reading mathematical text requires readers to engage with all the structures of the book and with its pedagogical voice, making connections, and plausible reasoning. Specific practices and strategies that support the close reading of mathematical text have been suggested; however, descriptions and empirical evaluations of materials designed to support these activities are rare. We present the design and first evaluation cycle of materials developed in a design research project that aims to scaffold close reading of mathematical text. The materials were designed and evaluated in a German university course on elementary geometry for first-year teacher education students who study mathematics to become primary teachers. The reading strategies were explained and modeled for students in reading-strategy videos. Additionally, close reading of mathematical text was scaffolded by close-reading tasks and homework tasks and problems that build on the reading strategies and were specifically designed to foster understanding of the mathematical text. Survey data were collected from 296 students to evaluate their use of and attitude toward the different materials. The quantitative results indicate that students used the materials and were generally able to learn the course content by themselves. From all provided materials, they found the close-reading tasks most helpful. A qualitative analysis of answers to open questions revealed issues with different materials, particularly with the script, and requests for additional materials. The issues with the script were categorized inductively. The categories are presented as a qualitative result of the study and discussed.
Keywords: General Mathematics; Education

Editorial: Research on Data Science Education - Biehler, Rolf; De Veaux, Richard; Engel, Joachim; Kazak, Sibel; Frischemeier, Daniel (Statistics Education Research Journal)
A very warm welcome to this Special Issue of the Statistics Education Research Journal (SERJ) on data science education. Our hope is to give an overview of selected theoretical thoughts and empirical studies on data science education from a statistics education research perspective. Data science education is rapidly developing but research into data science education is still in its infancy. The current issue presents a snapshot of this developing field.
Keywords: Education; Statistics and Probability

Teaching and Learning Data-Driven Machine Learning with Educationally Designed Jupyter Notebooks - Fleischer, Yannik; Biehler, Rolf; Schulte, Carsten (Statistics Education Research Journal)
This study examines modelling with machine learning. In the context of a yearlong data science course, the study explores how upper secondary students apply machine learning with Jupyter Notebooks and document the modelling process as a computational essay incorporating the different steps of the CRISP-DM cycle. The students’ work is based on a teaching module about decision trees in machine learning and a worked example of such a modelling process. The study outlines the students’ performance in carrying out the machine learning technically and reasoning about bias in the data, different data preparation steps, the application context, and the resulting decision model. Furthermore, the context of the study and the theoretical backgrounds are presented.
Keywords: Education; Statistics and Probability

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Developing and Evaluating the Concept Data Awareness for K12 Computing Education - Höper, Lukas (21st Koli Calling International Conference on Computing Education Research)
Students often have a lack of understanding and awareness of where, how, and why personal data about them is collected and processed. Especially, when interacting with data-driven digital artifacts, an appropriate perception of the data collection and processing is necessary for self-determination. This dissertation deals with the development and evaluation of a concept called data awareness which aims to foster students’ self-determination interacting with data-driven digital artifacts.
Keywords: data awareness; machine learning; data science education; data-driven digital artifacts; artificial intelligence

Computers and Education – Recognising Opportunities and Managing Challenges - Passey, Don; Brinda, Torsten; Cornu, Bernard; Holvikivi, Jaana; Lewin, Cathy; Magenheim, Johannes; Morel, Raymond; Osorio, Javier; Tatnall, Arthur; Thompson, Barrie; Webb, Mary (Advancing Research in Information and Communication Technology)
Keywords: Educational technologies; Education and technologies; Digital technologies and education; Information technologies; Communication technologies; Educational technologies and research; Educational technologies and pedagogical practices; Educational technologies and policy; Educational management and technologies; Professional development and educational technologies

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years.Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Education

Berufswahlmotivation angehender Wirtschaftspädagog*innen: Validierung des FIT-Choice-Ansatzes und Exploration der Gründe für das Studium der Wirtschaftspädagogik - Goller, Michael; Ziegler, Simone (Zeitschrift für Berufsund Wirtschaftspädagogik)
National und international ist in den letzten Jahren ein vergrößertes Interesse an der Erforschung der Berufswahlmotivation von Studierenden des allgemeinen Lehramtes zu beobachten. Auch in der Wirtschaftspädagogik hat die empirische Auseinandersetzung mit den Beweggründen der Studien- und Berufswahl eine gewisse Tradition. Gleichzeitig muss bemängelt werden, dass die existierenden Untersuchungen einerseits bisher keine an die nationale und internationale Forschung anschlussfähigen Erhebungsinstrumente benutzten und andererseits regional nur einzelne Hochschulstandorte berücksichtigten. Die hier berichtete Studie nimmt sich dieses Forschungsdesiderates an. Hierzu wurden 879 Studierende der Wirtschaftspädagogik an zwölf deutschen Studienstandorten mit einem standardisierten Fragebogen, basierend auf dem bereits gut etablierten FIT-Choice-Ansatz, befragt. Auf Basis dieser Stichprobe werden folgende Forschungsfragen beantwortet: (1) Inwiefern eignet sich das FIT-Choice-Instrumentarium auch für Untersuchungen von Studierenden der Wirtschaftspädagogik?, (2) Welche Motive sowie Vorstellungen vom späteren Beruf liegen der Berufswahl der befragten Studierenden der Wirtschaftspädagogik zugrunde? und (3) Inwiefern unterscheiden sich die Berufswahlmotive sowie die Vorstellungen des späteren Berufs der befragten Wirtschaftspädagogikstudierenden in Hinblick auf das Geschlecht, eine vorherige Berufsausbildung sowie den späteren Berufswunsch? Die Validierung zeigt, dass sich der FIT-Choice-Ansatz größtenteils gut eignet, um auch Studierende der Wirtschaftspädagogik zu untersuchen. Darüber hinaus geben die Befunde vertiefte Einblicke in die Berufswahlmotivation angehender Wirtschaftspädagog*innen (z. B. hohe Relevanz des polyvalenten Studiencharakters).
Keywords: Berufswahl; Motivation; Wirtschaftspädagogik; Berufliche Bildung; FIT-Choice; Lehramt; Career Choice; Business; Education; VET; FIT-Choice; Teacher Education

Have Academics’ Citation Patterns Changed in Response to the Rise of World University Rankings? A Test Using First-Citation Speeds - Lee, Soo Jeung; Schneijderberg, Christian; Kim, Yangson; Steinhardt, Isabel (Sustainability)
Academics may actively respond to the expectations of the academic status market, which have largely been shaped by the World University Rankings (WURs). This study empirically examines how academics’ citation patterns have changed in response to the rise of an “evaluation environment” in academia. We regard the WURs to be a macro-level trigger for cementing a bibliometric-based evaluation environment in academia. Our analyses of citation patterns in papers published in two higher education journals explicitly considered three distinct periods: the pre-WURs (1990–2003), the period of WURs implementation (2004–2010), and the period of adaption to WURs (2011–2017). We applied the nonparametric Kaplan–Meier method to compare first-citation speeds of papers published across the three periods. We found that not only has first-citation speed become faster, but first-citation probability has also increased following the emergence of the WURs. Applying Cox proportional hazard models to first-citation probabilities, we identified journal impact factors and third-party funding as factors influencing first-citation probability, while other author- and paper-related factors showed limited effects. We also found that the general effects of different factors on first-citation speeds have changed with the emergence of the WURs. The findings expand our understanding of the citation patterns of academics in the rise of WURs and provide practical grounds for research policy as well as higher education policy.
Keywords: world university rankings; citation; first-citation speed; Minerva; Studies in Higher Education

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years. Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Work-Based Learning; Organisational Change; Digital Competences; Qualitative Research; Digitalisation; Farming; Dairy; VET; Vocational Education and Training

Das Praxissemester aus der Perspektive von Mentor*innen: Aufgaben der Lernorte und wahrgenommene Veränderungsbedarfe - Caruso, Carina; Goller, Michael (Lehrerbildung auf dem Prüfstand)
Mentor*innen unterstützen Studierende u.a. bei der Planung, Durchführung und Reflexion von Unterricht. Obwohl Mentor*innen ein hoher Einfluss auf die Professionalisierung angehender Lehrkräfte zugeschrieben wird, gibt es nur wenige Studien, in denen die Perspektive von Mentor*innen beforscht wird. Dieser Beitrag zielt darauf, die Perspektive von Mentor*innen zu den Aufgaben der am Praxissemester beteiligten Lernorte sowie Veränderungsbedarfe zu explorieren. Hierzu werden Ergebnisse einer Interviewstudie mit 23 Mentor*innen vorgestellt, die zur Beantwortung nachstehender Forschungsfragen beitragen: (1) Welche Aufgaben haben die am Praxissemester beteiligten Lernorte und die dort tätigen Akteur*innen hinsichtlich der Vorbereitung, Unterstützung und Begleitung der Studierenden im Praxissemester aus Perspektive befragter Mentor*innen? (2) Was sind aus Sicht von Mentor*innen Veränderungsbedarfe hinsichtlich der Rahmenbedingungen bzw. Konzeption des Praxissemesters? Ein zentraler Befund der Studie ist, dass allen Lernorten attribuiert wird, dass diese Studierende auf die praktische Unterrichtstätigkeit vorbereiten sollen. Die Relevanz der Universitäten wird dabei allerdings als gering eingeschätzt. Auch theoretisch-reflexive Aspekte spielen in den Aussagen der meisten Mentor*innen keine Rolle. Veränderungsbedarf wird von den Mentor*innen vor allem in der Rolle des Zentrums für schulpraktische Lehrerausbildung und der Universität gesehen. Diese Befunde werden anschließend kritisch diskutiert.
Keywords: Lehrerbildung; Mentoring; Praxissemester; Professionalisierung / internship; mentoring; professionalisation; teacher education

Zur Relevanz von Fallarbeit - Caruso, Carina; Woppowa, Jan (Religionspädagogische Beiträge. Journal for Religion in Education)
Der Beitrag verbindet die Sichtweisen verschiedener Professionalisierungsansätze mit der Frage nach der Gestaltung der (universitären) Begleitung angehender Lehrkräfte im Praxissemester. Dabei wird der Wert von Fallarbeit herausgearbeitet und beschrieben, wie eine Unterstützung angehender (Religions-)Lehrkräfte gestaltet sein müsste, um Entwicklung und Lernen im Praxissemester systematisch zu begleiten. Der Beitrag widmet sich daher zuerst den Rahmenbedingungen und Forschungsbefunden zu Langzeitpraktika und der Gestalt von Professionalisierung durch Praxis. Daran schließen sich Denkfiguren zur Unterstützung (religionspädagogischer) Professionalisierungsprozesse von angehenden Lehrkräften im Schulpraktikum durch rekonstruktive Fallarbeit an, aus Sicht etablierter Professionalisierungsansätze.
Keywords: Fallarbeit; Praxissemester; Professionalität; Professionalisierung; Lehrerinnen- und Lehrerbildung / casework; teacher education; internship; professionalization; professionalism

Exploring the impact of pre-service science teachers’ reflection skills on the development of professional knowledge during a field experience - Kulgemeyer, Christoph; Kempin, Maren; Weißbach, Anna; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (International Journal of Science Education)
Keywords: Education

Students in the spotlight: Using collaborative autoethnography to build a community of learning in the Corona crisis - Steinhardt, Isabel (ISA Pedagogy Series)
Due to the Corona crisis, German Higher Education Institutions had to close their campuses in March and lecturers had to teach online. To understand how the Corona crisis affected students, first this article explains the structural and social inequalities in the German higher education system, using Tinto's (1975; 1997) student engagement theory. Second, the concept of Bergman-Rosamond et al. (2020) is used to analyze the challenges that Corona has raised for students, including current surveys. We found that the closure of the social space campus (and the Corona crisis as a whole) particularly hit hard those students who had previously been affected by (intersectional) inequality. Therefore, to lessen the specific challenges associated with the ad hoc transition to digital studying, the creation of a digital community of learning can help. We demonstrate how such a community can be created by the example seminar, "Digital practices: an autoethnographic observation". During the seminar, students recorded their digital technology use in a journal, and we analyzed the diary entries using the collaborate autoethnography method. The seminar example shows that this method is well suited for the development of a community of learning as it not only places students in the spotlight but as students work together on a topic they get to know each other, and a basis of trust is created through peer-feedback. Therefore, it was important to have a digital space (in this case Mahara) where the exchange could take place. The continuous insight into the students’ "learning status" enabled the lecturer to promote the learning and provide individual assistance for the students.
Keywords: Intersectionality; inequality; gender; diversity; higher-education; crisis

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

The presence of students identified as having special needs as a moderating effect on their classmates’ reading comprehension scores in relation to other major class composition effects - Krammer, Mathias; Seifert, Susanne; Gasteiger-Klicpera, Barbara (Educational Studies)
Keywords: Education

Comparing digital to print assessment of receptive vocabulary with GraWo‐KiGa in Austrian kindergarten - Paleczek, Lisa; Seifert, Susanne; Schöfl, Martin (British Journal of Educational Technology)
Keywords: Education

Teaching and learning in a multilingual Europe: findings from a cross-European study - Dockrell, J. E.; Papadopoulos, T. C.; Mifsud, C. L.; Bourke, L.; Vilageliu, O.; Bešić, E.; Seifert, Susanne; Gasteiger-Klicpera, B.; Ralli, A.; Dimakos, I.; Karpava, S.; Martins, M.; et al. (European Journal of Psychology of Education)
Abstract School classrooms within the EU are multilingual learning environments. The diversity of pupils in classrooms raises significant challenges for teachers, but to date, there are no data from large-scale surveys that compare views within and across European countries. A bespoke questionnaire was designed to examine views of current classroom learning environments with respect to the multilingualism. The questionnaire was piloted and subsequently completed by 2792 teachers across different European countries. Eleven countries provided sufficient data for analyses. Results from structural equation modelling showed that teachers’ attitudes could be reliably measured across Europe with the use of carefully devised questionnaire, whose loading and factor structure remained invariant across countries. Teachers’ views about multilingualism were most challenged by the numbers of children in their classes, not the percentage of multilingual pupils in the class. Countries differed in how they perceived multilingualism, with their differences leading to distinctive country clusters. Gender and education level (elementary vs. secondary) differences were also observed irrespective of country. These findings enhance our understanding of the role that the characteristics of teachers and their classrooms play in a multilingual setting across diverse European settings. The practical relevance of the results and new opportunities for teacher training are discussed.
Keywords: Developmental and Educational Psychology; Education

Increasing the effect of a remedial mathematics course by switching to an online format during the COVID-19 crisis: evidence from a German university - Büchele, Stefan; Liebendörfer, Michael; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Due to the COVID-19 crisis, many courses have been offered digitally. Using data from n = 1,173 business students participating in a preparatory mathematics course at a German university that covered the same content as in 2018, 2019 and 2020, we examine how students’ participation and the effect of the preparatory course changed. The data show that the participation rate has fallen slightly, but students’ participation is rather similar to preceding years. Interestingly, students have participated more intensively. There are clear signs of dishonesty in the self-test (use of a calculator) and significant changes in predictors of performance. In particular, the effect of students’ engagement in the course on their performance substantially increased. Further, we found a gender gap in performance affecting women. Finally, the data show that digital courses can be as effective as on-campus courses.
Keywords: Education; General Mathematics

University students’ fully digital study of mathematics: an identification of student-groups via their resources usage and a characterization by personal and affective characteristics - Kempen, Leander; Liebendörfer, Michael (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract We investigated university students’ study of mathematics in the digital setting context of the COVID-19 pandemic. We gathered data from a survey of 89 students enrolled in a ‘Linear Algebra 1’ course including affective variables, learning strategies, social relatedness and resources considered useful. The results indicate students’ high effort and self-regulation and a high variation in affective characteristics and social relatedness. All the traditional aspects of mathematics teaching (lecture, tutorials and lecture notes) were rated as particularly useful. In addition, the videos from external resources were rated as equally useful as the teaching team’s videos. In contrast, traditional literature such as textbooks was rarely considered useful. The most useful resource rated was communication with peers, underlining the important role of social learning despite fully digital learning environments. Finally, a cluster analysis based on students’ rated usefulness of the resources led to three different user-types. Whereas the ‘digitals’ find the external digital resources very useful (videos, webpages, etc.), the ‘traditionalists’ rate the digitalized traditional resources best (lecture, tutorials, etc.). All resources receive uniformly good ratings from a third group (‘all resource users’). We reflect on our findings in light of the pandemic and describe directions for future research.
Keywords: Education; General Mathematics

Technological and Inclusive Education - Considering Students’ Needs Towards Technological Learning in Primary Schools - Schröer, Franz; Tenberge, Claudia (TECHNE SERIES - Forskning i slöjdpedagogik och slöjdvetenskap)
Research on technological educationininterdisciplinary scienceand socialstudies (Sachunterricht) in German primary schools emphasizes that childrenare generally interested in technology. While several STEAM initiatives point towards a growing recognition of technological literacy, the consideration of technology education ininterdisciplinaryscience and social studies is quite underrepresented in practice as well as in research and teacher training.Takinginto accountthe UN-CRPDclaims foran inclusive educational system andthus alsothe right to equally participate in a free society,participation in society through participation in technological development is a fundamental common goal of technological and inclusive education and part of widely recognized technological literacy.It is therefore not well understood how teaching and learning arrangementscan consider and satisfythe needs of all different students. The research project the present paper is part of tries to unveil the appearance of student’s basic needs in relation to technological educationfor all children. Thisinitial quantitative part of a grounded theory study examined the subjective significance of basic psychological needs in interdisciplinary science studies in primary educationto allow for a well-reasoned sample choice for subsequent interviews. Quantitative results point towards some revisions regarding the instrument used and several implications on the diversity of students ́needs in science and social studies. Future research is needed with larger samples for factor-analysis.
Keywords: Inclusion; basic needs; Technology Education; Primary Education; autonomy; competence; social relatedness

Building, emptying out, or dreaming? Action structures and space in students’ metaphors of academic writing - Scharlau, Ingrid; Karsten, A.; Rohlfing, Katharina J. (Journal of Writing Research)
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics; Education

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils F.; Crawshaw, Camilla E.; Rohlfing, Katharina (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.
Keywords: Education

Academic self-concept, perceptions of inclusion, special needs and gender: Evidence from inclusive classes in Sweden - DeVries, Jeffrey M.; Knickenberg, Margarita; Trygger, Maria (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education

Exploring the impact of pre-service science teachers’ reflection skills on the development of professional knowledge during a field experience - Kulgemeyer, Christoph; Kempin, Maren; Weißbach, Anna; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (International Journal of Science Education)
Keywords: Education

Conceptualising and measuring domain-specific content knowledge of early childhood educators: A systematic review - Bruns, Julia; Gasteiger, Hedwig; Strahl, Carolin (Review of Education)
The role of domain-specific content knowledge is discussed controversially for the early childhood context. Therefore, this review aims at untangling the research on domain-specific content knowledge for early childhood educators by systematically reviewing the conceptual and operational definition of and results on early childhood educators' content knowledge in different domains. Using the scientific databases ERIC, PsycInfo and Web of Sciences, we identified 36 studies on early childhood educators' domain-specific content knowledge. By comparing these studies, we found that conceptualizations of early childhood educators' content knowledge move on a continuum between a scientific related perspective and a practice related perspective. The scientific related perspective defines content knowledge as the knowledge of key concepts, facts and rules of the domain integrating knowledge taught in primary, secondary or upper secondary school. The practice related perspective includes knowledge of key concepts, facts and rules of the domain limited to the knowledge explicitly relevant for teaching in early childhood education as well as selected domain-specific knowledge of children and teaching. Our review shows that the results and implications drawn by the study authors depend on how these authors conceptualize early childhood educators' content knowledge on this continuum. Further research, therefore, needs to consider carefully how early childhood educators' content knowledge is conceptualized. The paper further discusses gaps in this research field, such as validating methods for measuring early childhood educators' content knowledge or implementing more rigorous experimental designs to examine effects of early childhood educators' content knowledge.
Keywords: content knowledge; domain-specific learning; early childhood education; teacher knowledge

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

A longitudinal analysis of the reciprocal relationship between academic procrastination, study satisfaction, and dropout intentions in higher education - Scheunemann, Anne; Schnettler, Theresa; Bobe, Julia; Fries, Stefan; Grunschel, Carola (European Journal of Psychology of Education)
Abstract Student dropout is a multi-causal process. Different theoretical models on student dropout consider dysfunctional study behavior (e.g., academic procrastination) and low study satisfaction as possible determinants of students’ dropout intentions during their university studies. However, these models neglect contemporary conceptualizations that assume reverse relationships between dropout intentions and other determinants of the dropout process. Until now, empirical evidence on these assumptions is scant. The present three-wave longitudinal study explored the reciprocal relationships between academic procrastination, study satisfaction, and dropout intentions over one semester. To this end, we used data of N = 326 undergraduate students enrolled in mathematics and law. Our latent cross-lagged panel model replicated existing empirical cross-sectional findings between the variables (i.e., academic procrastination, study satisfaction, and dropout intentions). Regarding the longitudinal relations, as expected, the cross-lagged effects showed that higher dropout intentions significantly related to subsequent higher academic procrastination and lower study satisfaction. Unexpectedly, academic procrastination did not significantly relate to subsequent dropout intentions. Additionally, higher study satisfaction significantly associated with subsequent higher dropout intentions—possibly due to unfulfilled expectations. Further, higher study satisfaction significantly related to subsequent higher procrastination—possibly due to more confidence among satisfied students. Our results broaden the view on dropout intentions as part of the dynamic interplay of student dropout determinants and the need to refine dropout models’ assumptions accordingly. Practically, realistic expectations seem important to reduce dropout intentions. Further, student counselors should have a closer look at the reasons for academic procrastination to develop individual solutions for this dysfunctional behavior.
Keywords: Developmental and Educational Psychology; Education

A first introduction to data science education in secondary schools: Teaching and learning about data exploration with CODAP using survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Abstract In this paper, we will describe an introduction to Data Science for secondary school students. We will report on the design and implementation of an introductory unit on “Data and data detectives with CODAP” in which secondary school students used the online tool CODAP to explore real and meaningful survey data on leisure time activities and media use (so‐called JIM‐PB data) in a statistical project setting as a starting point for data science. The JIM‐PB data set served as a valuable data set that offered meaningful and exciting opportunities for data exploration for secondary school students, and CODAP proved to be a valuable tool for the first explorations of this data.
Keywords: Education; Statistics and Probability

Geometrisches Begriffsverständnis in der Grundschule am Beispiel der Begriffe Viereck, Rechteck und Quadrat - Bruns, Julia; Unterhauser, Elisabeth; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Zu den ersten geometrischen Begriffen, die Kinder bereits im Elementar- und Primarbereich lernen, zählen u. a. Viereck, Rechteck und Quadrat. Studien zeigen, dass Lernende bereits früh individuelle Vorstellungen, sog. individuelle Begriffskonzepte, zu diesen Begriffen aufbauen. Zwar wird die Entwicklung von Begriffsverständnis in verschiedenen mathematikdidaktischen Stufenmodellen dargestellt, diese sind jedoch generisch und beschreiben nicht explizit die Entwicklung der ersten individuellen Begriffskonzepte von Lernenden zu Viereck, Rechteck und Quadrat. Aus empirischer Sicht liegen verschiedene Studien vor, die einzelne Aspekte der individuellen Begriffskonzepte von Lernenden unterschiedlicher Altersgruppen zu diesen Begriffen ausleuchten. Um Begriffsbildungsprozesse aus empirischer Sicht detaillierter entlang der jeweils vorherrschenden individuellen Begriffskonzepte zu beschreiben, fehlen insbesondere Studien in der Grundschule, die alle vier Klassenstufen betrachten und dabei differenzierte Erkenntnisse zu verschiedenen theoretischen Indikatoren des Begriffsverständnisses liefern. Daher geht die vorliegende Studie der Frage nach, welches Verständnis der Begriffe Viereck, Rechteck und Quadrat Schülerinnen und Schüler der Jahrgangsstufen 1, 2, 3 und 4 zeigen. Dazu wurde eine Quasi-Längsschnittstudie mit N = 456 Grundschulkindern (ca. 100 pro Jahrgangsstufe) durchgeführt. Die Ergebnisse geben detaillierte Einblicke in die individuellen Begriffskonzepte der Lernenden und zeigen, dass Lernende zunehmend Eigenschaften der Figuren berücksichtigen, jedoch individuelle Begriffskonzepte über lange Zeit auch prototypisch geprägt sind. Implikationen dieser Ergebnisse für Forschung und Praxis werden diskutiert.
Keywords: Education; General Mathematics

Technology-centred learning processes as digital artistic development: On the reciprocal effects of conceptual models, metaphors and presets - Neuhausen, Timo; Wernicke, Carsten; Ahlers, Michael (Journal of Music, Technology & Education)
This case study looks at a self-directed learning process of a professional classical-trained musician adopting a previously unknown digital-material musical device. In order to achieve the desired artistic result, the musician has to modify his music-related action in favour of the device’s calls for action, which are shown to him by a preset session. For this purpose, a specific interface relation must be established in the connection between the user and the device. The case study is contrasted with data from its framing research project. Findings include aspects as affirmation or degrees of unfamiliarity and their respective impacts on the subject’s action repertoires. A model of learning in the context of digital media or interfaces is introduced and discussed. It offers a specific potential for identifying particularities of how meaning and functionality of digital-material musical devices are embedded into everyday artistic contexts.
Keywords: Music; Education; Music Technology

The interplay of personal and contextual diversity during the first year at Higher Education: Combining a quantitative and a qualitative approach - Jenert, Tobias; Brahm, Taiga (Frontline Learning Research)
Research on student transition into Higher Education (HE) has taken different theoretical perspectives. First, studies investigated personal variables such as students´ self-efficacy, emotions and motivation regarding the transition from school to HE. A second strand of research focused on contextual variables, for instance college effectiveness research. With this paper, we combine both the personal and the contextual approach. We aim to investigate the interaction between personal and contextual diversity during the transition into HE, taking into account students’ diversity in particular with regard to gender and individual characteristics, such as self-efficacy. We explored the heterogeneity in students’ personal characteristics by conducting a latent profile analysis (LPA) based on students’ intrinsic motivation, self-efficacy and anxiety before entering Higher Education. LPA resulted in three distinct profiles, with significant differences in how students perceived the first year. This finding suggests that students’ personal characteristics when entering Higher Education influence how they experience the study environment. To investigate the interplay between individual and contextual differences in more detail, we conducted a qualitative longitudinal study with 14 first-year students in parallel with the panel survey. We found that individual students react very differently to specific characteristics and events of the first-year environment. Our study adds to the growing body of research that aims to grasp the complexity of interactions between individual and contextual differences. Specifically, we illustrate how combining quantitative and qualitative methods can provide new insights into person-context interactions.
Keywords: Education

Mathematics textbooks and curriculum resources as instruments for change - Rezat, Sebastian; Fan, Lianghuo; Pepin, Birgit (ZDM – Mathematics Education)
Abstract In this survey paper we aim to provide an overview of research on mathematics textbooks and, more broadly, curriculum resources as instruments for change related to mathematical content, instructional goals and practices, and student learning of mathematics. In particular, we elaborate on the following themes: (1) The role of curriculum resources as instruments for change from a theoretical perspective; (2) The design of curriculum resources to mediate the implementation of reform ideas and innovative practice; (3) Teachers’ influence on the implementation of change through curriculum resources; (4) Students’ influence on the implementation of change through curriculum resources; and (5) Evidence of curriculum resources yielding changes in student-related factors or variables. We claim that, whilst textbooks and curriculum resources are influential, they alone cannot change teachers’ teaching nor students’ learning practices in times of curricular change. Moreover, more knowledge is needed about features of curriculum resources that support the implementation of change. We contend that curriculum innovations are likely to be successful, if teachers and students are supported to co- and re-design the relevant curriculum trajectories and materials in line with the reform efforts and their own individual needs.
Keywords: General Mathematics; Education

How automated feedback from a digital mathematics textbook affects primary students’ conceptual development: two case studies - Rezat, Sebastian (ZDM Mathematics Education)
Abstract One of the most prevalent features of digital mathematics textbooks, compared to traditional ones, is the provision of automated feedback on students’ solutions. Since feedback is regarded as an important factor that influences learning, this is often seen as an affordance of digital mathematics textbooks. While there is a large body of mainly quantitative research on the effectiveness of feedback in general, very little is known about how feedback actually affects students’ individual content specific learning processes and conceptual development. A theoretical framework based on Rabardel’s theory of the instrument and Vergnaud’s theory of conceptual fields is developed to study qualitatively how feedback actually functions in the learning process. This framework was applied in a case study of two elementary school students’ learning processes when working on a probability task from a German 3rd grade digital textbook. The analysis allowed detailed reconstruction of how students made sense of the information provided by the feedback and adjusted their behavior accordingly. This in-depth analysis unveiled that feedback does not necessarily foster conceptual development in the desired way, and a correct solution does not always coincide with conceptual understanding. The results point to some obstacles that students face when working individually on tasks from digital mathematics textbooks with automated feedback, and indicate that feedback needs to be developed in design-based research cycles in order to yield the desired effects.
Keywords: General Mathematics; Education

Introducing students to machine learning with decision trees using CODAP and Jupyter Notebooks - Biehler, Rolf; Fleischer, Yannik (Teaching Statistics)
Keywords: Education; Statistics and Probability

Mathematics in Engineering Education: a Review of the Recent Literature with a View towards Innovative Practices - Pepin, Birgit; Biehler, Rolf; Gueudet, Ghislaine (International Journal of Research in Undergraduate Mathematics Education)
Abstract The aim of the special issue is to bring together important current international research on innovative teaching and learning practices in mathematics in engineering education, and to develop deeper understandings of the characteristics of current teaching and learning practices that can inform the design and implementation of future innovative practice. The focus of this review paper is to provide a state-of-the-art overview of this emerging field at the cross-roads between mathematics and engineering education, in addition to introducing the papers of this special issue. To guide this paper, we posed three review questions: (1) How can current (teaching/learning/study) practices of mathematics in engineering education be characterized with a view towards innovation?; (2) What are the ‘resources’ (cognitive, material, digital, social) used, and what are those that appear also well suited for innovative courses?; (3) What are promising innovative practices in mathematics in engineering education, and what are the implications for curriculum reform? Looking back across the studies we summarized in the review, we conclude that they are lagging behind the more fundamental changes that are happening in engineering education, whilst addressing selected aspects of innovative changes within the current system of engineering education. At the same time, the nine papers of this special issue contribute new perspectives for innovative practices in mathematics in engineering education, for a better understanding of current practices and for future research.
Keywords: Education; Mathematics (miscellaneous)

Consultation Phases in Mathematics Learning and Support Centres - Schürmann, Mirko; Panse, Anja; Shaikh, Zain; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Hilgert, Joachim (International Journal of Research in Undergraduate Mathematics Education)
Abstract Mathematics Learning Support Centres are becoming more and more common in higher education both internationally and in Germany. Whereas it is clear that their quality largely depends on a functioning interaction in consultations, little is known about how such consultations proceed in detail. On the basis of models from the literature and recorded support sessions (N = 36), we constructed a process model that divides consultations into four ideal–typical phases. In the individual consultations, forward or backward leaps occur, but overall the model seems to describe the data well. A high intercoder reliability shows that it can be applied consistently on real data by different researchers. An analysis of the consultations between students and tutors shows that both mainly work on past attempts or thoughts of the students to solve the exercise or problems and on concrete strategies to solve a problem within the session. In contrast, very little time is dedicated to summarizing and reflecting the solution. The data allows for a more in-depth discussion of what constitutes quality in advising processes and how it might be further explored. Practically, the model may structure support sessions and help in focussing on different goals in different phases.
Keywords: Education; Mathematics (miscellaneous)

The process of actively building a model for a randomization test – insights into learners’ modeling activities based on a case study - Podworny, Susanne; Biehler, Rolf (Mathematical Thinking and Learning)
Keywords: Developmental and Educational Psychology; Education; General Mathematics

A first introduction to data science education in secondary schools: Teaching and learning about data exploration withCODAPusing survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Keywords: Education; Statistics and Probability

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Learning Open Science by doing Open Science. A reflection of a qualitative research project-based seminar - Steinhardt, Isabel (Education for Information)
Openness in science and education is increasing in importance within the digital knowledge society. So far, less attention has been paid to teaching Open Science in bachelor’s degrees or in qualitative methods. Therefore, the aim of this article is to use a seminar example to explore what Open Science practices can be taught in qualitative research and how digital tools can be involved. The seminar focused on the following practices: Open data practices, the practice of using the free and open source tool “Collaborative online Interpretation, the practice of participating, cooperating, collaborating and contributing through participatory technologies and in social (based) networks. To learn Open Science practices, the students were involved in a qualitative research project about “Use of digital technologies for the study and habitus of students”. The study shows the practices of Open Data are easy to teach, whereas the use of free and open source tools and participatory technologies for collaboration, participation, cooperation and contribution is more difficult. In addition, a cultural shift would have to take place within German universities to promote Open Science practices in general.
Keywords: Open Science; Open Education Practices; Library and Information Sciences; Education; Information Systems

„Sie sind doch eine Medienklasse!“ - Caruso, Carina; Reis, Oliver (Österreichische Religionspädagogische Forum)
Ausgehend von Ergebnissen zur Mediennutzung und Ausführungen zur Medienkompetenz fokussiert der Beitrag digitale Praktiken im Religionsunterricht. Zur Analyse der mit der Digitalisierung verbundenen Transformation digitaler Praktiken wird die Akteur-Netzwerk-Theorie dargestellt sowie die Begriffe Digitalisierung und Digitalität definiert. Anhand einer Vignette (dichte Beschreibung) wird der Frage nachgegangen, wie sich Lehrkräfte auf Herausforderungen von Digitalität einlassen (können), inwiefern sie digitale Praktiken eröffnen und inwiefern diese mit traditionellen Praktiken verbunden sind.
Keywords: Digitale Praktiken; Digitalisierung; Medienkompetenz; Professionalisierung; Religionsunterricht / digital practices; digitization; digital literacy; teachers' professional development; religious education

Auswirkungen der Digitalisierung industrieller Arbeit auf die berufliche und allgemeine Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung am Übergang Schule Beruf Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Digitalisierung ist derzeit ein viel diskutiertes Thema. Mit ihr werden derart tief grei- fende Veränderungen der Gesellschaft und Arbeitswelt erwartet, dass sie häufig als digitale Revolution bezeichnet wird. Gleichzeitig wirft die Auseinandersetzung mit diesen antizipierten Veränderungen viele noch unbeantwortete Fragen auf. Diese umfassen unter anderem Überlegungen hinsichtlich des Substitutionspotenzials menschlicher Arbeit durch die Digitalisierung, die Frage nach der Ausgestaltung der Rolle des Menschen in der Industrie 4.0 und schließlich Erwägungen in Bezug auf die Vorbereitung und Begleitung von Beschäftigten in der digitalen Transformation. Der vorliegende Beitrag gibt Aufschluss über die Dimensionen der Digitalisierung und die derzeit diskutierten Entwicklungslinien; er befasst sich weiterhin mit den sich daraus ergebenden Herausforderungen und Bedeutungen für die industrielle Arbeit und die Beschäftigten. Abschließend werden daraus abzuleitende Implikationen für die berufliche und allgemeine Bildung diskutiert.
Keywords: Digitalisierung; Industrie 4.0; Arbeit 4.0; berufliche Aus- und Weiterbildung; allgemeine Bildung / digitalization; industry 4.0; work 4.0; vocational education and training; general education

Transforming study abroad: a handbook - Pöllmann, Andreas (Compare: A Journal of Comparative and International Education)
Keywords: Education

Technisches Lernen inklusiv gestalten – Zur Beschaffenheit von Lernbedürfnissen im Kontext technikbezogenen Sachunterrichts - Schröer, Franz (Technikunterricht: handfest und geistreich - Der Beitrag technischer Bildung zur kulturellen Bildung - Tagungsband zur 21. Tagung der Deutschen Gesellschaft für Technische Bildung in Flensburg vom 20.-21. September 2019. Offenbach am Main)
Der Gedanke einer inklusiven Schule als einer Schule für alle Kinder ist, wenn auch aus der Perspektive von 100 Jahren Grundschule erst kürzlich durch die UN-Konvention über die Rechte von Menschen mit Behinderung (United Nations 2006) verstärkt, als an das Bildungssystem gerichtete Anforderung unbestritten. Die Didaktik des Sachunterrichts als wissenschaftliche Disziplin und als Instanz technikbezogenen Lernens in der Grundschule hat sich dem Thema Inklusion mit den Untersuchungen von Seitz (2005) und Schomaker (2000), für eine fachdidaktische Disziplin vergleichsweise früh zugewendet (Pech & Schomaker 2013, S. 341). Pech, Schomaker & Simon (2018, S. 12ff.) arbeiten jedoch an begrifflichen Unschärfen in einschlägigen Veröffentlichungen heraus, dass es in der Sachunterrichtsdidaktik bis heute keinen systematischen Diskurs darüber gibt, wie Inklusion zu verstehen, zu entwickeln und zu implementieren ist. Die allgemeinpädagogisch unter anderem von Feuser (2011, S. 89) für das Bildungssystem formulierte Entwicklungsaufgabe von der Segregation über die Integration zur Inklusion findet sich in Abhängigkeit von der Perspektive unterschiedlich definiert in der Sachunterrichts- bzw. Fachdidaktik wieder. Da bei der Definition von inklusivem Sachunterricht unterschiedliche wissenschaftliche Kontexte (z.B. sonderpädagogische, inklusionspädagogische oder allgemeindidaktische) zur Argumentation herangezogen werden, ist im Folgenden häufiger von der Rekontextualisierung von Inklusion in der Fachdidaktik die Rede. Die Berücksichtigung von Lernbedürfnissen und die Nutzung von individuellen Potenzialen stellt eine sich in der Sachunterrichtsdidaktik (u.a. Lichtblau 2014, S. 204; Simon 2014, S. 241; Pech, Schomaker & Simon 2018, 15f.) wie in der allgemeinen Pädagogik (Feuser 1989, S. 9; Schumann 2009, S. 51; Preuß 2018, S. 81) wiederholende Rekontextualisierung zur Beschreibung inklusiven Unterrichts dar. Potenzialorientierte (fach-)didaktische Überlegungen, also solche, die eine Orientierung an in Personen liegenden Defiziten auf der einen und standardisierten Normen auf der anderen Seite ablehnen und den Blick vermehrt auf die im Individuum, dem Fach oder einem Lerngegenstand liegenden Potenziale für eine gleichberechtigte und gleichwertige Partizipation aller Lernenden richten (Simon 2019, S. 114), erfahren derzeit vermehrt Aufmerksamkeit. Die Berücksichtigung individueller Lernbedürfnisse auf der anderen Seite bleibt in einschlägigen Veröffentlichungen dagegen oftmals theoretisch unreflektiert. Ausgehend davon leistet das vorgestellte Dissertationsvorhaben mit Blick auf technikbezogenes Lernen im Sachunterricht der Grundschule einen theoriebildend angelegten Beitrag zur Verbindung von erziehungswissenschaftlicher und sachunterrichtsdidaktischer Inklusionsforschung am Lerngegenstand Technik. Die Studie ist, ob der Offenheit des Forschungsfeldes bezogen auf technikbezogenen Sachunterricht im Kontext von Inklusion, überwiegend qualitativ-rekonstruktiv angelegt. Unter der Rekontextualisierung von Inklusion als Berücksichtigung zunehmend vielfältiger Lernbedürfnisse im Sachunterricht, fragt die Studie nach der Beschaffenheit und Dimensionen der Verschiedenheit von Lernbedürfnissen sowie Möglichkeiten bzw. Hindernissen auf dem Weg zu ihrer Berücksichtigung.
Keywords: Inclusion; Sachunterricht; basic needs; technology education

Ethical Considerations of Applying Robots in Kindergarten Settings: Towards an Approach from a Macroperspective - Tolksdorf, Nils F.; Siebert, Scarlet; Zorn, Isabel; Horwath, Ilona; Rohlfing, Katharina J. (International Journal of Social Robotics)
In child–robot interaction (cHRI) research, many studies pursue the goal to develop interactive systems that can be applied in everyday settings. For early education, increasingly, the setting of a kindergarten is targeted. However, when cHRI and research are brought into a kindergarten, a range of ethical and related procedural aspects have to be considered and dealt with.While ethical models elaborated within other human–robot interaction settings, e.g., assisted living contexts, can provide some important indicators for relevant issues, we argue that it is important to start developing a systematic approach to identify and tackle those ethical issues which rise with cHRI in kindergarten settings on a more global level and address the impact of the technology from a macroperspective beyond the effects on the individual. Based on our experience in conducting studies with children in general and pedagogical considerations on the role of the institution of kindergarten in specific, in this paper,we enfold some relevant aspects that have barely been addressed in an explicit way in current cHRI research. Four areas are analyzed and key ethical issues are identified in each area: (1) the institutional setting of a kindergarten, (2) children as a vulnerable group, (3) the caregivers’ role, and (4) pedagogical concepts. With our considerations, we aim at (i) broadening the methodology of the current studies within the area of cHRI, (ii) revalidate it based on our comprehensive empirical experience with research in kindergarten settings, both laboratory and real-world contexts, and (iii) provide a framework for the development of a more systematic approach to address the ethical issues in cHRI research within kindergarten settings.
Keywords: Robot ethics · Kindergarten settings · Child–robot interaction · Early childhood education

Professional knowledge affects action-related skills: The development of preservice physics teachers’ explaining skills during a field experience - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (Journal of Research in Science Teaching)
Keywords: Education

Situative Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mathematik – Entwicklung und Validierung eines Testinstruments - Bruns, Julia; Strahl, Carolin; Gasteiger, Hedwig (Unterrichtswissenschaft)
Zusammenfassung Frühe mathematische Bildung findet in der Kindertagesstätte insbesondere in spontanen Alltagssituationen statt. Damit diese Alltagssituationen zu natürlichen Lernsituationen für die Kinder werden, müssen (angehende) frühpädagogische Fachkräfte zunächst das mathematische Potenzial in diesen Situationen erkennen. Diese Fähigkeit zur situativen Beobachtung und Wahrnehmung ist bisher unzureichend erforscht, was unter anderem auf begrenzte Methoden zur standardisierten Erfassung dieses Konstrukts zurückzuführen ist. Um diesem Bedarf zu begegnen, wurde das videobasierte Testinstrument Vimas_num zur Erfassung der Fähigkeit zur situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mengen und Zahlen entwickelt. Auf der Grundlage von drei aufeinander aufbauenden Studien wird die Validität verschiedener Aspekte der Testwertinterpretation untersucht. Die Ergebnisse geben Hinweise auf die Validität der Testwertinterpretation in Bezug auf den Testinhalt, die interne Struktur des Tests und die Zusammenhänge mit theoretisch verbundenen Konstrukten.
Keywords: Education

Christian Efing / Karl-Hubert Kiefer (Hg.): Sprachbezogene Curricula und Aufgaben in der beruflichen Bildung. Aktuelle Konzepte und Forschungsergebnisse - Prikoszovits, Matthias (Deutsch als Fremdsprache)
Keywords: Computer Science Applications; History; Education

Motivation of out-of-field teachers for participating in professional development courses in mathematics - Lünne, Steffen; Schnell, Susanne; Biehler, Rolf (European Journal of Teacher Education)
Keywords: Education

Students’ Understanding of the Derivative Concept in the Context of Mathematics for Economics - Feudel, Frank; Biehler, Rolf (Journal für Mathematik-Didaktik)
Abstract The derivative concept plays a major role in economics. However, its use in economics is very heterogeneous, sometimes inconsistent, and contradicts students’ prior knowledge from school. This applies in particular to the common economic interpretation of the derivative as the amount of change while increasing the production by one unit. Hence, in calculus courses for economics students, learners should acquire an understanding of the derivative that is mathematically acceptable and connected to their prior knowledge, but which also takes into account its practical use in economics. In this paper we first develop a theoretical model describing such an understanding of the derivative for economics students. We then present an exploratory study investigating the extent to which economics students have such an understanding after their calculus course. The results indicate that many of them might not have acquired this kind of understanding, in particular concerning the common economic interpretation of the derivative. The study furthermore yields possible gaps in students’ understanding and possible misconceptions.
Keywords: Education; General Mathematics

Mathematics learning support centres in Germany—an overview - Schürmann, Mirko; Gildehaus, Lara; Liebendörfer, Michael; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard; Kuklinski, Christiane; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Mathematics learning support centres (MLSC) are widely established and evaluated in English-speaking countries (such as the UK, Ireland and Australia). In most of these countries, several national surveys on MLSCs exist. They give an overview of the number of MLSCs as well as their characteristics in these countries. In Germany, there is a lack of studies on MLSCs and the landscape of MLSCs has not been described yet. This article presents basic information concerning counts of MLSCs and their characteristics at universities. Based on a three-step approach of analysing university homepages and additional personal contact via email or phone calls, we gathered typical MLSC features (e.g. staff quantities and qualification, opening and support hours, supported study programmes). We analysed 190 universities from a web-based register on study programmes. In total, we found 61 MLSCs located at 51 German universities. Another 16 support centres were specialized on mathematics didactics, which means they focussed on didactical and methodological support for preservice teacher students and often provided different teaching materials. Thirty-eight centres were located at universities (62.3%) and 23 MLSCs at universities of applied sciences and comparable universities (37.7%). The MLSCs were different in their sizes of staff and opening hours, and both the numbers of staff and the service hours differed greatly. The student groups MLSCs at German universities focus on differ concerning characteristics like study programme or semester. We will provide the main categories describing these groups. We seek to answer research questions concerning the characteristics of MLSCs in Germany and discuss the results compared to international findings. This information is useful for further international collaborative research, for example a standardized international survey. From a national perspective, these findings support networking and collaborations between the MLSCs as well. As some German MLSCs are facing financial cuts, these results might help in gaining additional funding.
Keywords: Education; General Mathematics

Liberating or indoctrinating? Surveying students’ perceptions of a Womens’ and Gender Studies requirement - Horwath, Ilona; Diabl, Christian (Gender and Education)
This article offers new insight into students’ responses to Womens’ and Gender Studies (WGS) classes by overcoming the self-selection bias hitherto inherent in the field. Exploring the experiences of 1406 students (770 women, 636 men) of a university with a WGS requirement across all study programmes, we examine the prevailing discourses on WGS, participants’ (dis)agreement as well as personal and professional benefits gained through WGS. Additionally, we evaluate the perceived value of WGS for themselves, in society, and of WGS opportunities in higher education. Findings reveal a gender bias regarding discourses, experience, benefit, and value, with 70.1% women and 32.4% men supporting the idea of WGS as a mandatory subject. Women’s support indicates a need for tools to negotiate gender issues, while men’s resistance serves to defend male privileges. We conclude that a requirement of WGS classes amplifies the potential for both – resistance and change.
Keywords: Education policy; equality; higher education; critical pedagogies; gender mainstreaming; curriculum

Assessing dimensions of inclusion from students’ perspective – measurement invariance across students with learning disabilities in different educational settings - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin; Schwab, Susanne; Gebhardt, Markus (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education

European educational research (re)constructed: institutional change in Germany, the United Kingdom, Norway, and the European Union - Pöllmann, Andreas (Compare: A Journal of Comparative and International Education)
Keywords: Education

Gamification in an Augmented Reality Based Virtual Preparation Laboratory Training - Alptekin, Mesut; Temmen, Katrin (The Challenges of the Digital Transformation in Education)
Through technological progress during recent years, Augmented Reality (AR) technology can be used on ordinary smartphones with applications (Apps) in many formal and informal learning environments and educational institutions (e.g. [1, 2]). It is emerging as a suitable technology for teaching psychomotor skills. Simultaneously, gamification has become increasingly popular in the teaching field, providing famous examples, such as Duolingo (for the acquisition of foreign languages) or Codecademy (for learning programming languages) [3]. Many papers have already highlighted the beneficial aspects of gamification and AR for education and teaching (e.g. [1, 2, 4, 5]. While gamification is useful for improving students’ motivation and engagement, AR can be applied to teach them operational skills without any time, costs and place constraints. Hence, this opens up numerous possibilities and forms to combine these two aspects (AR and gamification) for higher education teaching. However, there has been less research focusing on how gamification and AR can be combined in a useful manner to keep up students’ initial motivation aroused through novelty effects of AR learning environments. Accordingly, this paper will present such a gamification concept for an AR based virtual preparation laboratory training to overcome the risk of demotivation, once AR will settle as a mainstream technology such as learning videos. The focus of the AR-App – presently being developed at the University of Paderborn – is to remedy the students’ lack of practical skills when operating electro-technical laboratory equipment during their compulsory laboratory training.
Keywords: Augmented Reality; Laboratory Training; Engineering Education; Gamification

Teaching an Oscilloscope through Progressive Onboarding in an Augmented Reality Based Virtual Laboratory - Alptekin, Mesut; Temmen, Katrin (2019 IEEE Global Engineering Education Conference (EDUCON))
The first impression is important in many aspects of human decision-making. In mobile apps, this impression can be influenced by an onboarding process. In addition, not only the user experience (UX) can be improved via onboarding, but also the user can get a very good didactical introduction to a new topic or different functionalities of an app. Therefore, this study examines different onboarding types and develops an onboarding process into an Augmented Reality (AR) based mobile application (app) that teaches students how to use and operate electro-technical laboratory equipment. This onboarding process is then assessed by students through a subsequent questionnaire in terms of attractiveness, functionality, and novelty. The results of this field study serve to examine this first prototype for possible optimizations and to further develop the app accordingly.
Keywords: Augmented Reality; Laboratory Training; Engineering Education; Progressive Onboarding

Vocabulary in learning processes towards conceptual understanding of equivalent fractions—specifying students’ language demands on the basis of lexical trace analyses - Wessel, Lena (Mathematics Education Research Journal)
Abstract Although the teaching of vocabulary in mathematics lessons is requested in content- and language-integrated lesson designs, the clarification of the specific lexical language demands is still an open question for many mathematical topics. In a content- and language-integrated lesson design towards understanding the concept of equivalent fractions, the vocabulary (words and phrases) used by 17 students has been analyzed with qualitative means of data analysis. The qualitative in-depth analyses underline the importance of meaning-related vocabulary for making structural relations between the fractions in view explicit. Quantitative analyses of inventoried vocabulary for the four categories “self-initiated by students,” “triggered by teaching material,” “triggered by teacher,” or “triggered by peers” show the relations of collective and autonomous vocabularies from which the students retrieve their lexical means in oral and written language production.
Keywords: Education; General Mathematics

How theories of language-responsive mathematics can inform teaching designs for vocational mathematics - Wessel, Lena (Eleventh Congress of the European Society for Research in Mathematics Education (CERME11))
Keywords: Vocational education; language; percentages; scaffolding; design research

Language diversity and mathematics education: new developments - Barwell, Richard; Wessel, Lena; Parra, Aldo (Research in Mathematics Education)
Keywords: General Mathematics; Education

FROM EMPOWERMENT TO INNOVATION: INTER- AND TRANSDISCIPLINARY RESEARCH METHODS IN LIGHTWEIGHT ENGINEERING - Horwath, Ilona; Dohmeier-Fischer, Silvia; Weiß-Borkowski, Nathalie; Tröster, Thomas (INTED2018 Proceedings)
Inter- and transdisciplinary research are new demands in Higher Education. Aiming to enhance the social relevance, usability and sustainability of technological products and solutions, society and public institutions such as research funding organizations increasingly expect engineers to include inter- and transdisciplinary approaches into the development of new technologies. Engineering research and education, however, are particularly challenging areas to realize inter- and transdisciplinary collaborations, for manifold reasons. This contribution presents methods and results of an inter- and transdisciplinary research and education strategy designed to meet the particular requirements of engineers and engineering students. It starts with a brief discussion of typical challenges regarding inter- and transdisciplinary approaches in engineering (research topics, research culture, skills, time, and barriers of lay people to involve in technology development). Secondly, it presents the methods developed to overcome those challenges within the context of the NRW Fortschrittskolleg "Light - Efficient - Mobile" (FK LEM). Founded in 2014, the FK LEM is a PhD programm focuses on lightweight construction, but with a special emphasis on how lightweight technologies are connected to different areas of society, to societal actors and technology users, and to the needs of a diversity of social groups. In order to explore these connections, we organized three workshops to bring public service, civil society, industry, practitioners and engineers together to discuss the perceived needs in those areas, and the potential of lightweight solutions. Topically, the workshops were dedicated to the fields of Rescue & Security Services; Care, Mobility & Assisted Living; and Sustainable Ressources & Climate Protection. Methodologically, we applied a pragmatic but valid approach to focus groups and discourse analysis. Results of the workshops in terms of directions for future research, epistemological and ethical dimensions of lightweight engineering are presented in the third part of our contribution. Finally, we discuss how our method and experience can be transferred into other engineering and educational contexts. With other words, how empowering students, engineers and the public to involve in inter- and transdisciplinary engineering processes can be achieved, and how this empowerment supports the development of innovative technologies as well as engineers’ skills to design technology in line with societies’ needs and challenges.
Keywords: Lightweight Design; Interdisciplinarity; Transdisciplinarity; Higher Education; Research Methods

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

La formación intercultural de los futuros maestros mexicanos de secundaria - Pöllmann, Andreas (Revista Electrónica de Investigación Educativa)
La provisión de oportunidades para el aprendizaje intercultural a través del contacto con “lo extranjero” es fundamental para el bienestar cultural, social y económico de los países multiculturales. El contexto mexicano es de particular interés tanto por su extraordinaria diversidad sociocultural como por sus niveles epidémicos de analfabetismo intercultural. Con base en una encuesta realizada a 189 estudiantes de la Escuela Normal Superior de México, el presente artículo explora (i) la importancia percibida del contacto con “lo extranjero” como parte de la formación magisterial, (ii) el interés existente por la participación en algún programa de intercambio internacional y (iii) el nivel de experiencias concretas con “lo extranjero”. A partir de una serie de estadísticas descriptivas –que demuestran las percepciones, intereses y experiencias de los futuros maestros de secundaria– se manifiesta la importancia de un mayor compromiso institucional y gubernamental con la formación intercultural del magisterio normalista.
Keywords: Education

Evaluating Innovative Measures in University Mathematics – The Case of Affective Outcomes in a Lecture focused on Problem-Solving - Kuklinski, Christiane; Leis, Elena; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Neuhaus, Silke; Schaper, Niclas; Schürmann, Mirko (Proceedings of the Second Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2018, 5-7 April 2018))
The transition from high school to university mathematics has proven to be difficult for many students but especially for pre-service secondary teachers. To support these students at mastering this transition, various universities have introduced support measures of various kinds. The WiGeMath project developed a taxonomy that makes it possible to describe and compare these measures concerning their goals as well as their frame characteristics. We will exemplify the use of the taxonomy in the description of one specific innovative measure that was part of the WiGeMath evaluations. Moreover, we will present first results concerning the goal-fulfilment of this measure concerning affective characteristics of the student cohort and their predominant beliefs.
Keywords: Beliefs.; Motivational developments; Novel approaches to teaching; Teacher education; Transition to and across university mathematics